Investigation of military nursing through the cinema : Pearl Harbor - Pedro Manuel Salas Iglesias (Universidad de Alicante, 2012)
The axis of this methodological-scientific investigation will be the historical moment of the U.S.A incursion in World War II, following the Japanese bombing to the main North American base in the Pacific, Pearl Harbor. The military cinema as mass media, becomes a useful tool for extracting the social image of nursing during the development of war conflicts, this image maintaining a historical-cultural relation with them. This film is articulated according to Florence Nightingale´s nursing model.